Humboldt's enigma viewed through the lens of ecosystem theory. Explanation by simple principles - Nielsen, S. N. (2022)
The observation that mountain regions generally display higher diversity than tropical regions has recently been presented as a puzzle or “enigma”, since it seems to contradict the normal belief that the highest diversity on Earth occurs in the rain forest ecosystems around the equator. The observation seems to be well supported by data gathered for several animal and plant communities, and thus deserves further attention, including investigation of how it arises. However, re-interpretation of the enigma in the light of ecosystem theory serves to resolve the problem, explaining the increased diversity as the result of the presence of a larger set of thermodynamic and thermo-chemical variables, which vary in quantity, quality, time, and space, together with the forcing functions usually present. This permits a more intensive exploitation of the gradients in an oscillating environment as formulated for instance in the intermediate disturbance hypothesis combined with the niche construction concept. Put simply, mountain regions offer an environment with a greater and more variable set of gradients, in terms of both quantity and quality, than occur in the more stable environments found in relatively flat areas. This gives an extra stimulus to speciation processes, resulting in the elevated diversity observed. © 2021 The Authors